DEIKSIS DALAM FILM ENOLA HOLMES KARYA HARRY BRADBEER (SUATU ANALISIS PRAGMATIK) - Tandean, Marselino Danovan; Pamantung, Rina P.; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â This research is entitled â€œDeiksis dalam Film Enola Holmes Karya Harry Bradbeerâ€. There are 5 types of deixis, those are: person deixis (first person, second person, and third person), place deixis, time deixis, discourse deixis, and sosial deixis. Deixis belongs to pragmatics. The word deixis come from the Greek deiktikos, it means, â€œpointingâ€. The objectives of this research are to identify and classify the types of deixis and to analyze the function of deixis in the film Enola Holmes by Harry Bradbeer. The method used in this research is descriptive method. The data are identified, classified and analyzed descriptively. The data were analyzed based on Levinson theory. The result shows that there are five types of deixis in the film Enola Holmes, those are person (first person: I, me, mine, our, we, us, and my; second person: your, yours and you; third person: he, him, they, and them), place deixis: here, there, this train, this house time deixis: ago, tomorrow, next time, later,and now, discourse deixis: this, and sosial deixis: madam, master, sir, uncle, brother, and mother. Thios rsearch also shows the functions of each deixis. It is expected that this research will help the students and the other readers to learn the pragmatics aspects, especially about deixis.Keywords: Film, Pragmatics, Deixis.